EFFECTS OF CUTTING PARAMETERS ON CUTTING FORCE AND CHIP SHRINKAGE COEFFICIENTS IN HIGH-SPEED MILLING OF ALUMINUM ALLOY A7075 - Pham Thi Hoa; Tran Viet Hoi; Phan Ngoc Tuan; Phan Dang Thuc (Journal of Applied Science and Technology, 2022)
This paper uses John-Cook material model to simulate by finite element method the high-speed milling of aluminum alloy A7075. Then the effects of cutting parameters, including cutting speed, depth of cut, and tool’s clearance angle on the cutting force and chip shrinkage coefficient, are analyzed. Applying Taguchi and ANOVA methods, the study also found the optimal cutting parameters for F and K of high-speed milling corresponding: V = 1,695 (m/min), t = 1.0 (mm), α = 15º and V = 1,695 (m/min), t = 1.5 (mm), α = 15º. The result of K and F after simulation with obtained parameter set is 1.43 and 51.63 (N), when using Taguchi Gray method to minimize F and K and the common set of parameters are V = 1,695 m/min, t = 1 mm, α = 15º.